Ubiquitin-specific peptidase-19 links TDP-43 aggregation to ER stress - Yan Yan; Xinming Wang; Hanna Jeon; Teresa R. Kee; Khoi D. Tran; Hyunkyoung Lee; Xingyu Zhao; Tian Liu; Simon S. Wing; Jung-A A Woo; David E. Kang (Proceedings of the National Academy of Sciences, 2026)
Aggregation and deposition of TAR DNA-binding protein 43 (TDP-43) is a salient pathological signature of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration-TDP (FTLD-TDP). TDP-43 proteostasis and aggregation are controlled by several posttranslational modifications, including ubiquitination. While multiple E3 ubiquitin ligases are known to facilitate TDP-43 clearance, little is known about the role of deubiquitinases (DUBs) in controlling TDP-43 proteostasis. Through an unbiased discovery screen of DUBs, here we identify and demonstrate using in vitro and in vivo models, as well as human brain tissue, that ubiquitin-specific peptidase-19 (USP19) acts as a TDP-43-directed DUB that removes K48- and K63-linked ubiquitin conjugates from TDP-43 and preferentially promotes cytoplasmic aggregation of TDP-43 C-terminal fragments (TDP-CTFs) through its catalytic activity. Specifically, the endoplasmic reticulum (ER)-anchored USP19 isoform (USP19-ER) exhibits superior activity in deubiquitinating TDP-CTFs, enhancing its phase separation and aggregation, compared to its cytosolic isoform (USP19-Cyto). Furthermore, as TDP-CTFs are generated at the ER, USP19 acts to couple the aggregation of TDP-CTFs to ER stress (ATF6, ATF4, IRE1, & CHOP). In humans, USP19 protein levels increase in FTLD-TDP brains, which extensively colocalize with cytoplasmic phospho-TDP-43 (pTDP-43) pathology. Importantly, we demonstrate in vivo that genetic reduction of usp19 mitigates pTDP-43 pathology, astrogliosis, and ER stress while reversing long-term potentiation (LTP) and motor deficits in a mouse model of TDP-43 pathogenesis (TAR4 mice). These findings establish a critical role of USP19 at the nexus of TDP-43 proteostasis and ER stress, implicating its pathogenic role in FTLD-TDP and ALS.